2018
DOI: 10.1007/s40097-018-0288-z
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of Terminalia arjuna-conjugated palladium nanoparticles (TA-PdNPs) and its catalytic applications

Abstract: Synthesis of metal nanoparticles from the metal salts by reduction with plant extracts in water, without any additional stabilizing or capping agents is a green and eco-friendly method. In the present work, aqueous extract of the bark of Terminalia arjuna was utilized to synthesize T. arjuna-conjugated palladium nanoparticles (TA-PdNPs) from palladium chloride. The dark brown colour indicating the formation of TA-PdNPs appeared within 3 h without heating but, on heating colour appeared almost instantly. The sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The shapes of the synthesized PdNPs were mostly spherical along with triangular, hexagonal etc. 9 Bark extract of Cinnamomum zeylanicum also been utilized to prepare spherical shaped PdNPs of size 15-20 nm. 3 The fruit extract of Gardenia jasminoides have been utilized to fabricate spherical PdNPs of size 3-5 nm.…”
Section: Physicalmentioning
confidence: 99%
See 2 more Smart Citations
“…The shapes of the synthesized PdNPs were mostly spherical along with triangular, hexagonal etc. 9 Bark extract of Cinnamomum zeylanicum also been utilized to prepare spherical shaped PdNPs of size 15-20 nm. 3 The fruit extract of Gardenia jasminoides have been utilized to fabricate spherical PdNPs of size 3-5 nm.…”
Section: Physicalmentioning
confidence: 99%
“…PdNPs synthesized from bark extract of Terminalia arjuna utilized to perform Heck reaction of iodobenzene and methyl acrylate in presence of triethyl amine as base in aqueous DMF system at 90 o C. The reaction completed within 5 hours with 95.5% yield. 9 PdNPs supported on several polymers or inorganic backbones shows excellent catalytic activity and they are easily recoverable for the presence of solid supports. PdNPs supported on triazine functionalised meso porous covalent organic polymer used as catalyst for cross coupling reaction between several substituted aryl halides with styrenes and acrylates.…”
Section: Heck Cross Coupling Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding NP synthesis mediated by an extract from plants, it was suggested that the reduction of metallic salts could be carried out by flavonoid molecules such as apigenin and luteolin [51]. Additionally, these molecules and phenols provide stability in the nanoparticle formed [52,53].…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
“…2021, 11, x FOR PEER REVIEW 11 of 18 been reported by PdNPs synthesized using protein ferritin from Pyrococcus furios as a stabilizer [66]. The degradation of MB at a low rate due to a large kinetic energy barrier has been reported [52]. Many factors influence MB degradation, such as pH and the presence of amine groups [67].…”
Section: Nanoparticles Reactivity Characterizationmentioning
confidence: 99%